On the viability, cytotoxicity and stability of probiotic bacteria entrapped in cellulose-based particles. (September 2018) - Singh, Poonam; Medronho, Bruno; Santos, Tiago dos; Nunes-Correia, Isabel; Granja, Pedro; Miguel, Maria G.; Lindman, Björn
Abstract: Probiotics are increasingly gaining popularity in vast food applications due to their recognized health benefits to the host. However, their passage through the gastrointestinal (GI) tract is not smooth and a significant number of physiological barriers (e.g. low pH, bile salts, enzymes, peristaltic movements, etc.) may considerably affect their viability. The entrapment of probiotics in protective matrices, such as hydrogel particles, is a feasible approach to minimize cell death. Therefore, in this work, novel cellulose/chitosan-based particles have been developed to entrap model probiotic Lactobacillus rhamnosus GG. The particle aging, storing and stability was studied at different temperatures and in simulated GI fluids with and without cross-linking agents or protein and lipid additives. Moreover, the effect of the particles on a model intestinal cell line was evaluated. The formulations containing casein displayed the best bacterial survival/culturability when exposed to the GI fluids. Overall, the storage and viability of the probiotics were observed to be improved in the different biopolymer-based systems, generally presenting a low toxicity profile to the cell line. Thus, the particles, which were based on carboxymethyl cellulose and chitosan, may be regarded as interesting matrices for probiotic encapsulation and delivery in food products. Graphical abstract: Image 1 Highlights: Novel cellulose/chitosan-based particles for probiotic entrapment and delivery. Casein improves the colloidal stability and minimizes particle aggregation. Systems show appreciable LGG culturability when exposed to simulated GI fluids. Notable bacterial survival after storage for 30 days at different temperatures. Particles display low toxicity profile to a colon Caco-2 cell line.